2011
DOI: 10.4166/kjg.2011.58.2.82
|View full text |Cite
|
Sign up to set email alerts
|

Shifting in Seroprevalence of HBsAg and Anti-HCV during Recent 10 Years in Adults Resident in Daegu and Gyeongbuk Province

Abstract: The seroprevalence of HBsAg in Daegu/Gyeongbuk province was 4.8% and showed no difference through the time period of 10 years. The seroprevalence of anti-HCV was 0.5% and also showed no difference through the time periods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
2
3
0
Order By: Relevance
“…The seropositivity of HBsAg in this study increased with age from 20 to 40 years old, then decreased thereafter, which is comparable to other reports [Chae et al, ; Kim et al, ]. The reasons for decreasing seroprevalence in those over age 50 may be related to the natural loss of HBsAg and death from liver diseases such as cirrhosis or hepatocellular carcinoma [Lee et al, ]. Concerning the geographic differences of HBsAg seroprevalence in Korea, a previous study reported similar HBsAg seropositivity in several administrative areas with the exception of Jeju, where HBsAg seropositivity was approximately three times higher and anti‐HBs positivity significantly lower than those of the national average in 1998 [Lee et al, ; Kang et al, ].…”
Section: Discussionsupporting
confidence: 87%
“…The seropositivity of HBsAg in this study increased with age from 20 to 40 years old, then decreased thereafter, which is comparable to other reports [Chae et al, ; Kim et al, ]. The reasons for decreasing seroprevalence in those over age 50 may be related to the natural loss of HBsAg and death from liver diseases such as cirrhosis or hepatocellular carcinoma [Lee et al, ]. Concerning the geographic differences of HBsAg seroprevalence in Korea, a previous study reported similar HBsAg seropositivity in several administrative areas with the exception of Jeju, where HBsAg seropositivity was approximately three times higher and anti‐HBs positivity significantly lower than those of the national average in 1998 [Lee et al, ; Kang et al, ].…”
Section: Discussionsupporting
confidence: 87%
“…In Korea, the seropositivity of HBsAg in this study increased with age from 20 to 40 years old, and then decreased thereafter, which is comparable to other reports (Chae et al, 2009;Kim et al, 2009;Lee et al, 2013). The reasons for decreasing seroprevalence in those over age 50 may be related to the natural loss of HBsAg and death from liver diseases such as cirrhosis or hepatocellular carcinoma (Lee et al, 2011).…”
Section: Discussionsupporting
confidence: 85%
“…In particular, P. guillermodeltoroi was almost exclusively found in peri-urban sites and therefore we suggest that that specific population from the urban core could be at high risk in such a small habitat. Lee et al (2019) reported a minimum size of suitable habitat of 0.0039 km 2 for terrestrial fireflies from Daegu and Gyeongbuk provinces in South Korea. In contrast, Picchi et al (2013) reported green areas greater than 0.023 km 2 for two species of fireflies from the city of Turin, Italy.…”
Section: Discussionmentioning
confidence: 99%
“…Slope has been found to be a relevant variable of fireflies’ habitats because larvae are frequent on soggy ground and around ponds, marshes and streams which are usually found in flat plains or very gentle slopes ( Lloyd, 2002 ; Kazama et al, 2007 ; Lee et al, 2019 ). Therefore, we expected that fireflies from Morelia would also be more frequent in flat plains, which cover about half of the city and used to be rice paddy fields ( López et al, 2001 ; López Núñez & Pedraza Marrón, 2012 ).…”
Section: Discussionmentioning
confidence: 99%